Analisis Perpindahan Panas Pada Peralatan Pengering Multi Tingkat Secara Numerik - Fikri, Thaharul; Syuhada, Ahmad; Thaib, Razali; Bahri, Samsul (Rekayasa Material, Manufaktur dan Energi, 2025)
Drying equipment is a device commonly used to remove moisture from various materials, particularly food products, to extend their shelf life and usability. However, in multi-tier drying systems, a common issue is the non-uniform temperature distribution between levels. This problem arises due to the uneven distribution of hot gas from the fuel source, causing the temperature on racks closer to the heat source to be higher than those on upper levels. To address this issue, heat ducts and fins were added to each level. The fins serve to evenly distribute heat from the hot gas channels throughout the drying chamber. Due to the high costs associated with experimental testing, this study adopts a numerical approach. The numerical simulation is conducted using Computational Fluid Dynamics (CFD) via SOLIDWORKS 2022 to analyze fluid flow and heat transfer within the dryer. The results indicate that the nine-level dryer remains operationally efficient, with the lowest temperature difference (∆T) recorded at 1.6°C when operating at 60°C.